Composed Indicator of Community Forest Governance in San Miguel Topilejo, Mexico City - Susana Aguilar-Martínez (MDPI AG, 2021)
Community Forest Governance is a process of building agreements and decision-making about rules and norms for the use and access to forest resources of common use. The main objective of this study was to know the level of governance about the management and conservation of the forest of the agrarian community of San Miguel Topilejo, in Southern Mexico City. A survey was applied to a representative sample of 58 community members. The level of governance is determined by a composed indicator that includes criteria and specific indicators of social capital, collective action, and local organization. The main finding shows that social capital is low because there is little cohesion between community members. Community collective action shows a lack of cooperation and coordination to enforce norms and sanctions in the use of forest resources. The level of organization is low because the structure of positions and roles is very basic and not specialized. The conclusion is that the level of governance is low because this community has no clear common objectives, there is a lack of well-established norms and sanctions, and there is a lack of involvement of owners in the decision-making process and management of forest resources of common use.